DETECTION OF PESTICIDES RESIDUES CHLORPYRIFOS IN SOME MEDICINAL PLANTS (Academicia Globe: Inderscience Research, 2023)
Pesticide deposits were measured in few of the genrally used, restorative plants gathered from various business sectors namely: green tea, red tea, sfof, senmaki, cinnamon, nutmeg, chewing mixture and slimming mixture where it was found that malathion, pyrimifos-methyl, and profenofos were predominant in most of them during the measurement. In these samples, the presence of fungicides was detected only in cumin samples, where it was dominated by samples of cumin, anise, tea, sage, especially organophosphate pesticides (chlorpyrifos, profenofos, pyrimifos, methyl and ethion), and ginger parts were with ought pesticides, while cinnamon samples showed only chlorpyrifos